O negócio das chacinas: sentidos de justiça, privatização da segurança e corrupção policial em São Paulo - Silva, David Esmael Marques da (Universidade Federal de São Carlos, 2021)
This doctoral study takes as its empirical focus the “chacina”— initially defined here as incidents of multiple homicide involving three or more victims within a single event—that occurred in Osasco and Barueri, municipalities in the metropolitan region of São Paulo, on August 13, 2015, in which 19 homicides were committed in peripheral urban areas by groups of hooded individuals. Following investigation and judicial proceedings, the case resulted in the conviction of three military police officers and one municipal guard from Barueri. However, on appeal, a second jury trial was ordered, in which one military police officer and the municipal guard were acquitted. Through this case study, the thesis seeks to better understand what constitutes a “chacina”, in order to reflect on the reasons why police officers become involved in such crimes in São Paulo, as well as the competing conceptions of justice that surround these events. To this end, the research draws on information about the case, its investigation, and judicial processing as reported in the press, as well as on direct observation of stages of the judicial proceedings and part of the jury trial. It also incorporates quantitative data on “chacinas” and related phenomena in São Paulo and Brazil, in addition to interviews with representatives of institutions within the criminal justice system, including the Civil Police, Military Police, Public Defender’s Office, and Police Ombudsman’s Office in the state of São Paulo. The findings indicate that chacinas are mobilized within different grammars of social conflict in Brazil, particularly since the 1990s, with those perpetrated by police officers—whether on or off duty—constituting one identifiable type. Furthermore, although the Osasco and Barueri “chacina”, carried out by off-duty police officers, was initially interpreted as an act of revenge for the killing of a military police officer and a municipal guard in the same region days earlier, the analysis ultimately reveals conceptions of justice associated with the business of providing private security services by police officers to commercial establishments. In this sense, public and private logics become intertwined, as public agents act off duty in pursuit of personal profit. Finally, the thesis proposes a typology of “chacinas” in general, as well as a specific typology for those involving police officers.
The business of “chacinas”: conceptions of justice, privatization of security, and police corruption in São Paulo
Keywords: Chacinas - São Paulo; Violência policial; Sistema de justiça criminal; Segurança privada ilegal; Sistema de justiça criminal - Descrédito; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; 16. Paz, Justiça e Instituições Eficazes